Clinical determinants of insulin requirements during treatment of prednisolone-induced hyperglycaemia. (March 2023) - Chen, Angela X.; Radhakutty, Anjana; Zimmermann, Anthony; Stranks, Stephen N.; Thompson, Campbell H.; Burt, Morton G.
Abstract: Aims: The optimal treatment of prednisolone-associated hyperglycaemia is unclear, but guidelines recommend using a body weight-based daily insulin dose. This study evaluated how clinical variables were associated with insulin requirements in hospitalised patients with prednisolone-associated hyperglycaemia. Methods: In this prospective study, fifty adult inpatients who were taking prednisolone ≥20 mg/day and experienced hyperglycaemia were prescribed a 24-h intravenous insulin infusion. The daily insulin dose required to attain a mean glucose of 8 mmol/L was calculated. The associations between daily insulin dose and clinical variables were assessed. Results: The participants age was 69 ± 10 years, daily prednisolone dose was 34 ± 10 mg, HbA1c was 7.7 ± 2.0 % (61 ± 10 mmol/mol), 77 % had known type 2 diabetes and 30 % were female. In univariate analysis, weight was associated with daily insulin dose (r 2  = 0.11, p = 0.024). A multivariate model comprising sex, HbA1c, a prior diagnosis of diabetes, diabetes treatment and weight explained nearly-two thirds of the variability in daily insulin dose (r 2  = 0.65, p < 0.001). Conclusions: In patients with prednisolone-associated hyperglycaemia, calculating insulin doses based on sex, HbA1c, diabetes status and regular diabetes treatment and weight may improve glycaemic control compared to weight-based dosing.